Analisis Representasi Visual: Kajian Kekerasan Simbolik dalam Film - Munawaroh; Guatri, Gaia (Journal of Religion and Film, 2023)
This study discusses the analysis of visual representation in films with a study focus on symbolic violence. This article uses literature study to show a comprehensive picture regarding visual representation and symbolic violence in films. This article finds first, symbolic violence and visual media shows the impact of visual media, such as television and film, in shaping people's perceptions of violence and how it can be represented symbolically. Second, symbolism in films as a tool to provide a deeper dimension to the story. Symbolism in film is explored as a secret language that enriches the cinematic experience, shapes character, and opens the door to diverse interpretations. Overall this study emphasizes the importance of understanding and critical analysis of visual representations in the media, as well as exploring the diversity of meanings through symbolism in films. Thus, analysis of film visual representations provides broad insight into the study of symbolic violence and symbolism in the cinematic world.